2016 IEEE 84th Vehicular Technology Conference (VTC-Fall) 2016
DOI: 10.1109/vtcfall.2016.7881122
|View full text |Cite
|
Sign up to set email alerts
|

On the Number and 3D Placement of Drone Base Stations in Wireless Cellular Networks

Abstract: Using drone base stations (drone-BSs) in wireless networks has started attracting attention. Drone-BSs can assist the ground BSs in both capacity and coverage enhancement. One of the important problems about integrating drone-BSs to cellular networks is the management of their placement to satisfy the dynamic system requirements. In this paper, we propose a method to find the positions of drone-BSs in an area with different user densities using a heuristic algorithm. The goal is to find the minimum number of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
281
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 394 publications
(309 citation statements)
references
References 12 publications
0
281
0
1
Order By: Relevance
“…The authors in [3] showed that the UAV-BS placement in the horizontal dimension can be modeled as a circle placement problem and a smallest enclosing circle problem, and they proposed an optimal 3D placement algorithm for maximizing the number of served users with the minimum transmit power. In [4], a method using the heuristic algorithm for finding the positions of UAV-BSs in an area with different user densities was proposed. This algorithm can estimate the minimum number of UAV-BSs and their placement, while satisfying coverage and capacity constraints.…”
Section: Related Workmentioning
confidence: 99%
“…The authors in [3] showed that the UAV-BS placement in the horizontal dimension can be modeled as a circle placement problem and a smallest enclosing circle problem, and they proposed an optimal 3D placement algorithm for maximizing the number of served users with the minimum transmit power. In [4], a method using the heuristic algorithm for finding the positions of UAV-BSs in an area with different user densities was proposed. This algorithm can estimate the minimum number of UAV-BSs and their placement, while satisfying coverage and capacity constraints.…”
Section: Related Workmentioning
confidence: 99%
“…One of these is backhaul connectivity between the UAV-BSs and the core network, which may impact the overall system performance. While various algorithms for optimized UAV-BS deployment have been proposed in recent literature [4], [5], there is a lack of comprehensive studies considering all of the important factors under practical modeling assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…In a dynamic communications network, the link quality between the user and the UAV-BS will vary with the wireless channel, user mobility, communication scenarios, and the location and altitude of the UAV-BS. The key to finding the effective location and height of the UAV-BS with high communications quality is the ability to quickly learn and identify the characteristics of the current 3D wireless channel [1] [2].…”
Section: Introductionmentioning
confidence: 99%